Legal-Political Study of the Job Creation Law on Revocation of Article 20 of Law Number 13 of 2016 concerning Patents - Anisa Ribut Septihana; Luluk Lusiati Cahyarini (Borobudur Law Review, 2022)
Patent protection in Indonesia today still leaves various problems, both practical (implementation) and conceptual (acceptance by the public). While, the Indonesian government took a place to settle the issues on the patent by revoked the provision on the Patent Law into the Omnibus Law Number 11 of 2020 on Job Creation (UU Cipta Kerja). The purpose of this research is to analyse the enactment of Omnibus Law (UU Cipta Kerja) as the revocation of Article 20 of Law Number 13 of 2016 concerning Patents. This research is dogmatic research with a statute approach and a conceptual approach. This research found that, the law plays a very important role in the life of the state, therefore ideally every law enforced must reflect (rechtside) and the national ideals (staatside) of the Indonesian nation. This is in the context of realizing social justice, fostering a united society, realizing just material and spiritual welfare, and achieving a proportional balance. The abolition of the content of Article 20 of the 2016 Patent Law in the Job Creation Law actually contains the assumption of an oligarchic interest in it